Polymyxin B and Doxycycline for Treatment of Multidrug Resistant Klebsiella Pneumoniae and Staphylococcus Aureus Pneumonia in Intensive Care Unit - Keyal, Niraj Kumar; Nakarmi, Manish; Adhikari, Pooja (Birat Journal of Health Sciences, 2019)
Doxycycline is a broad spectrum antibiotic. We hereby report a case report of patients that developed multidrug resistant hospital acquired pneumonia. Patients were treated with Polymyxin B and Doxycycline. From this we want to emphasize that Doxycycline can be used as alternative agent in combination with Polymyxin B for treatment of multidrug resistant pneumonia although there are no large scale studies on combination of Polymyxin B and Doxycycline.